QUALITY INDICATORS OF AUTOMATIC REGULATION SYSTEMS OF DRILLING MODES OF OIL AND GAS WELLS WITH ELECTRIC DRILLS - Шавранський, Михайло; Дмитрик, Тарас (SWorldJournal, 2024)
This work analyzes automatic regulation systems, which include a bit feed regulator, designed for efficient operation of electric drills during well drilling. The main purpose of the system is to maintain the specified power value on the electric drill mo